2011
DOI: 10.1002/aenm.201000050
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Develop Safe All‐Inorganic Monolithic Li‐Ion Batteries

Abstract: Li-ion batteries based on liquid electrolytes have conquered the electronics marketplace, however, cost and safety are the overriding parameters limiting their widespread use in electric vehicles (EVs) or hybrid EVs (HEVs). [ 1 ] Ideally, Li-ion batteries should rely on the use of dry polymer or inorganic electrolytes, as they would then be free of solvent leakages. The former are still under development after many years of research and the latter currently fall short in terms of high impedance issues associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
113
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 21 publications
0
113
1
Order By: Relevance
“…Although adding fire retardant (FR) additives to lower the flammability of the liquid electrolytes can, to some extent, reduce the flammability of liquid organic electrolytes, 20 the recently emerging solid state electrolytes, which function as both electrolyte and separator, may be the most promising option for current or next-generation LIBs with enhanced safety and reliability. 10,[80][81][82] From the battery tester's point of view, the present investigation may open up new opportunities for future standard battery testing procedures. Conventional mechanical evaluation techniques have been criticized because they only show how the cells behave under an abuse condition instead of truly replicating the conditions of a field failure.…”
Section: Comparison Of the Amount Of Lms Determined By Morphological mentioning
confidence: 99%
“…Although adding fire retardant (FR) additives to lower the flammability of the liquid electrolytes can, to some extent, reduce the flammability of liquid organic electrolytes, 20 the recently emerging solid state electrolytes, which function as both electrolyte and separator, may be the most promising option for current or next-generation LIBs with enhanced safety and reliability. 10,[80][81][82] From the battery tester's point of view, the present investigation may open up new opportunities for future standard battery testing procedures. Conventional mechanical evaluation techniques have been criticized because they only show how the cells behave under an abuse condition instead of truly replicating the conditions of a field failure.…”
Section: Comparison Of the Amount Of Lms Determined By Morphological mentioning
confidence: 99%
“…A large number of sintered materials have been tested until now among which we can cite: metals and alloys, intermetallics, carbides, borides, nitrides, silicides, oxides, sialon, ceramic-metal and ceramic-intermetallic composites, ceramic-ceramic composites, hydroxyapatite-based materials, chalcogenides, polymer-based materials, functional graded materials, systems for joining, graphite/carbon-based materials including composites containing carbon-nanotubes, multi-materials including solid state batteries (Aboulaich et al, 2011) and other systems. A review of the materials tested can be found elsewhere Orru et al, 2009).…”
Section: State Of the Art Of The Materials Investigatedmentioning
confidence: 99%
“…The extent of the initial imperfect contact depends on the fabrication processes. For example, two type of batteries can be synthesized by different manufacturing processes, film-type [13][14][15] and bulk-type [16][17][18] batteries. The former one usually uses deposition process and forms the amorphous structure with a less rough surface, resulting in a better interface contact than the latter one, which is commonly formed by pressing particles and has much rougher interfaces.…”
mentioning
confidence: 99%